Sustained modes in a waveguide having an annular core cross-section with non-concentric circular boundaries - Singh U.K.; Khastgir P.; Singh O.N. (My University, 2025)
In an earlier communication we reported an analytical study of the modal cutoff behaviour of a waveguide having an annular core cross-section bounded by two non-concentric circles. Here a detailed study of the characteristic equation has been made. We discuss a number of cases with different parameters (dimensions and the refractive indices of the core and the cladding) for this waveguide. In this study we find that v = 3 is the least possible value of the modal index for real values of the propagation constant β i.e. for unattenuated modes. Further, as one increases the modal index v, the β value increases. Also in order to decrease the modal index v for a possible mode it is necessary to reduce the refractive index difference (n1-n2) for a fixed dimension of the waveguide. Results show that the present structure supports fewer modes than the concentric annular cross-section waveguide.